The INFLUENCE OF COUNSELING ON FIBROADENOMA MAMMAE (FAM) ON THE SKILLS OF EARLY DETECTION THROUGH SADARI ACTION IN 4TH SEMESTER STUDENTS OF THE OBSTETRICS STUDY PROGRAM D-III STUDENT HIGH SCHOOL OF HEALTH SCIENCE BHAKTI MULIA PARE KEDIRI - Wahyurini, Sulistyo Dewi (Jurnal Delima Harapan, 2024)
Background: Fibroadenoma Mammae (FAM) is a type of benign tumor that is often found in the female breast. Early detection with the SADARI (Breast Self Examination) method is an effective preventive measure to identify any abnormalities in the breast early on. The purpose of the study was to determine the effect of counseling about FAM on early detection skills through SADARI actions in STIKes Bhakti Mulia Pare Kediri students in 2023. Method: Pre-experiment research design One Group Pre-Post Test Design approach. The population was all fourth semester students and a sample of 36 respondents using random sampling technique . The independent variable is counseling, and the dependent variable is the skill of early detection of fibroadenoma mammae (FAM) and SADARI action. Counseling was provided in accordance with the SAP. SADARI skills were observed using an observation sheet. Data were analyzed using Wilcoxon Signed Rank test. Results: The results of the study before counseling, 1 respondent (2.77%) had good skills in performing SADARI, while 28 respondents (77.77%) had sufficient skills, and 7 respondents (19.44%) had poor skills. After counseling, there was a significant increase in respondents' skills. A total of 29 respondents (80.54%) showed good skills in performing SADARI, while 4 respondents (11.11%) had sufficient skills, and 3 respondents (8.33%) were still categorized as lacking skills. The results of the Wilcoxon test obtained a p-value = 0.000 < α = 0.05, which means that there is an effect of the effect of counseling on FAM on early detection skills through SADARI actions on STIKes Bhakti Mulia Pare Kediri students in 2023. Conclusion: Interventions in the form of health counseling have a positive impact on increasing the knowledge and practical skills of female students. Education on early detection of FAM needs to be continued to increase awareness and skills of adolescent girls in preventing and identifying breast health risks early on